Parthasarathian Transient Solution of M/M/1 Queue Manifold: Info-Geometric Analysis and Applications to Machine Learning - A Mageed, Ismail (Optimality, 2024)
By constructing the Fisher Information Matrix (FIM) and its inverse (IFIM), the current study provides an info-geometric characterization of the transient M/M/1 queue manifold. Furthermore, stability's effect on IFIM's existence and its investigation of the Geodesic Equations (GEs) of motion have been made clear. Potentially even more, the article highlights several info-geometric machine learning applications. This in essence would manifest the huge contributions provided by this paper, which would in turn open new plethora of unlimited opportunities to the exploration of new trends in machine learning. In closing, some difficult open problems are discussed along with the next stage of the research.